IMPLEMENTASI PEMANFAATAN KAHOOT DALAM PEMBELAJARAN KEPULAUAN INDONESIA UNTUK MENINGKATKAN LITERASI TEKNOLOGI DAN MOTIVASI BELAJAR SISWA - Rahma Ayu Fauziyah; Oman Hadiana; Tio Heriyana; Nanan Abdul Manan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education plays an important role in developing students' knowledge, skills, and learning motivation. However, conventional learning methods that rely heavily on lectures and textbooks often make students feel bored and less engaged in the learning process. Therefore, the integration of technology in learning is needed to create a more interactive and engaging learning environment. This study aims to examine the implementation of the Kahoot learning media in teaching the topic of Indonesian archipelago, as well as its effect on students' technological literacy and learning motivation. This research used a mixed methods approach with a sequential explanatory design, combining quantitative and qualitative methods. The research was conducted at Sanggar Bimbingan At-Tanzil Putra Kajang, Kuala Lumpur, Malaysia, involving nine third-grade students as research subjects selected through purposive sampling. Data were collected using pretest and posttest, questionnaires, and interviews with the class teacher. Quantitative data were analyzed using descriptive statistics and paired sample t-test with the help of SPSS, while qualitative data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results of the study show that the implementation of Kahoot in learning can create a more interactive and enjoyable learning atmosphere, making students more active and enthusiastic in participating in the lesson. The findings also indicate an increase in students’ learning outcomes, with the average score rising from 4.11 in the pretest to 8.89 in the posttest. The paired sample t-test result shows a significance value of 0.000 < 0.05, indicating a significant effect of Kahoot on students’ learning outcomes. In addition, the use of Kahoot contributes to improving students’ learning motivation and technological literacy. Therefore, Kahoot can be considered an effective digital learning medium to support interactive and technology-based learning.